Revisiting the principles of Gharar (uncertainty) in Islamic banking financing instruments with special reference to bay al-inah and bay al-dayn- towards a new modified model - Razali, Siti Salwani (Publishing India Group, 2012)
One of the significant features of Islamic banking is the elimination of riba and gharar. However many problems arise in some of Islamic banking financing instruments when they are claimed to contain significant elements of gharar thus held unacceptable in certain Muslim countries. Among these instruments are Bay al-Inah and Bay al-Dayn. Currently, Bay al-Inah is not accepted in some countries such as the Middle East countries as it is regarded as part of interest-based transaction. However, in Malaysia, Bay al-Inah has been formalised as a permissible practice and is has emerged as the most important mode of transactions that stimulates the growth of Islamic transaction in Malaysia, which finally comes across the globe to be among the most successful Muslim state in the development of Islamic Finance. On the other hand, Bay al-dayn or the sale of debt is not unanimously accepted or validated by Muslim scholars. Even though some scholars allow it in all forms and aspects, the others either disallow it entirely or allow it under certain circumstances and with certain clauses or conditions.The paper will discuss at length on both contracts and the legal implications of the presence of gharar on the validity of these contracts. The views from the jurists will be critically examined to revisit the existence of gharar especially in these two Islamic banking instruments namely bay al-dayn and bay al-inah.